Acaricidal activity of thymol against larvae of Rhipicephalus microplus (Acari: Ixodidae) under semi-natural conditions - Araujo, Laryssa Xavier; Lopes Novato, Tatiane Pinheiro; Zeringota, Viviane; Matos, Renata Silva [UNESP]; Souza Senra, Tatiane Oliveira; Maturano, Ralph; Azevedo Prata, Marcia Cristina; Daemon, Erik; Oliveira Monteiro, Caio Marcio (Springer, 2015)
This is the first study to investigate the activity of thymol on Rhipicephalus microplus larvae under semi-natural conditions. For this purpose, tests were conducted in pots with Brachiaria decumbens seedlings containing cattle tick larvae. Thymol, diluted in ethanol 50A degrees GL, was tested at concentrations of 2.5, 5.0, 10.0, 15.0, and 20.0 mg/mL, along with the control group treated with the solvent alone. Each treatment was composed of five pots (1 pot = a repetition). The experiment was performed in three steps. On the first day, the larvae were applied at the base of the signalgrass. Twenty-four hours later, approximately 25 mL of the solution was applied with thymol on the top of the vegetation in each pot. The survival of the larvae was measured 24 h after application of the solutions. Each pot was analyzed individually, and the grass fillets contained larvae were cut with scissors, placed in Petri dishes, and taken to the laboratory to count the number of living larvae. At the highest concentrations (10, 15, and 20 mg /mL), the number of live larvae declined by more than 95 % in relation to the control group. The lethal concentration 50 % (LC50) and LC90 values were 3.45 and 9.25 mg/ml, respectively. The application of thymol in semi-natural conditions starting concentration of 10 mg/mL significantly reduced the number of living R. microplus larvae.
Keywords: Cattle tick; Brachiaria decumbens; Semi-natural conditions; Monoterpene